2017
DOI: 10.1080/02688697.2017.1301379
|View full text |Cite
|
Sign up to set email alerts
|

Nerve sheath myxoma of the oral cavity: a distinct entity

Abstract: Nerve sheath myxomas (NSM) are uncommon benign tumours of nerve sheath origin. These tumours are most often located in the dermis and subcutaneous tissue of the head and neck region, but less frequently can also involve extracutaneous sites but they are rarely seen in the oral cavity. Many authors consider nerve sheath myxoma and neurothekeoma to be variants of the same tumour, though currently it has been demonstrated that both the lesions are distinct entities with different origins and unique morphological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…NSM usually arises from the small peripheral nerves, and the involvement of the oral mucosa is rare 44,45 . NSM is characterized by a myxoid tissue organized in nodules of varying shape and size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NSM usually arises from the small peripheral nerves, and the involvement of the oral mucosa is rare 44,45 . NSM is characterized by a myxoid tissue organized in nodules of varying shape and size.…”
Section: Discussionmentioning
confidence: 99%
“…NSM usually arises from the small peripheral nerves, and the involvement of the oral mucosa is rare. 44,45 NSM is characterized by a myxoid tissue organized in nodules of varying shape and size. The myxoid nodules are typically hypocellular with an abundance of Alcian blue-positive ground substance, 44 resembling, in parts, OFM.…”
Section: F I G U R E 2 Macroscopic Appearance Of Oral Focal Mucinosismentioning
confidence: 99%
“…Immunohistochemically, neurothekeomas are positive for EMA and are negative for S-100 and GFAP and their most favored sites include head and neck, where it presents as a solitary mass. [6]…”
Section: Discussionmentioning
confidence: 99%
“…Intraoral NSM is a rare benign tumor, first reported in 1974 [4], with a small additional number of cases reported to date [1,3,[5][6][7][8][9][10][11][12][13][14]. In 1980, Gallager and Helwig [15] introduced the term neurothekeoma to describe a superficial tumor of presumed nerve sheath derivation which exhibited many clinical and histological similarities to NSM [1].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review published in 2013 identified only 25 clearly documented intraoral cases of NSMs [1]. Since that publication, to the best of our knowledge, only two additional cases of intraoral NSM have been published [2,3]. Given the extreme rarity of this intraoral tumor, the aim of this study was to present a case of NSM affecting the tongue in a 43-year-old female.…”
Section: Introductionmentioning
confidence: 99%